Do accelerated ventures learn what really matters? : an exploratory study of the Portuguese Ecosystem - Castro, José Pedro Freire Vieira de (2017)
Entrepreneurs are drivers for economic prosperity and innovation. They take risks that are normally avoided by established companies, pushing industry boundaries to the next level. Several incubation mechanisms emerged in order to support new ventures in coping with initial challenges. Accelerators were born in 2005 and completely revolutionized how business incubation is done. By offering knowledge intensive and specialized support, acceleration programs aim to speed up new ventures´ development in approximately three months. Scholars have studied this new incubation mechanism over the last years but still little is known about the impact that accelerators have on startups. In order to address this research gap, we interviewed ten accelerated startups to understand the entrepreneurs´ perspective about the program. Based on acknowledged research, we investigated the impact of accelerators on the drivers of startup success. Literature divides the drivers in four main categories – Team, Product, Marketing and Financials. We found accelerators to be remarkable Team Builders for accelerated startups. Due to the cohort effect and the knowledge-sharing environment promoted by accelerators, ventures develop their Team Personality and Credibility throughout the program. Additionally, we found that accelerators are great Market Development Champions for high-tech startups. Our results suggest that the accelerators´ market-oriented mindset positively impact all the drivers of startup success of the Marketing category.